Sanitation and personal hygiene among residential employees of brick factory. - Maharjan, Merina (2012)
ABSTRACT: About 1.6 million deaths every year can be attributed specifically unsafe water, poor sanitation, and lack of hygiene. In Nepal annually some 13,000 children under five die of diarrheal disease due to poor hygiene and sanitation. Nepal continues to bear the loss of some 10 billion rupees each year. The residential employees of brick factory reside in poorly managed cottage in large number, so there is high chance of getting infectious disease if their sanitation and personal hygiene condition is not good. The general objective of this study was to assess the knowledge and practice of sanitation and personal hygiene of residential employees of brick factory. The study design was cross sectional descriptive and explorative study which was carried out in brick factories of Imadole VDC, Lalitpur and Satungal, VDC, Kathmandu. All 80 households of residential employees residing at premises of brick factory were taken. Semi-structured questionnaires were used to interview the residential employees along with checklist for observation. The collected data was edited manually and analyzed by using Statistical Package for Social Sciences (SPSS) version 16 for windows. From study it was found that, the practice of water purification was among 19 percent. Toilets were used by 42.5 percent of respondent for defecation. Hand washing after defecation was present among 80 percent. Good practice of waste disposal burning and burying was found among 16.2 percent and 22.5 percent respectively. Waste water was disposed by throwing around home by 55 percent. The mean number of brushing of teeth per day is 0.99 and bathing per week was 1.9. In last 3 month 48.89 percent were suffered from diarrhea. The knowledge regarding sanitation and personal hygiene were found to be slightly good among radio holders and literate. The practice was found to be unsatisfactory among literates also. We can see some where there is lack of information and another way education and awareness is not being applied in sufficient manner.